Evaluation of Plastic Waste Management in Rawajati Waste Storage Depots, South Jakarta - Algafari Rizkyprima; Ananto Kusuma Seta; Desy Safitri; Achmad Husen (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to analyze and evaluate plastic waste management policies at the Rawajati Waste Storage Depot, South Jakarta. Based on the research results, it can be concluded that the policy manager stated the aim of creating a healthy and clean community environment from plastic waste from the plastic waste management policy at the Rawajati Waste Storage Depot, South Jakarta. The problem with this plastic waste management policy is the need for more public awareness to help manage plastic waste, and many people still need help to throw rubbish carelessly. Standardization of activities in this plastic waste management policy, namely reduce, reuse, and recycle. Officers collect rubbish from the community, then sort out which rubbish can still be used, and there is also rubbish that is then recycled again. Then, the level of change that has occurred in the management of plastic waste at the Rawajati Waste Storage Depot, South Jakarta, has become better, and there has been a high commitment to waste management. The observed changes result from these activities or other causes of waste management in Rawajati Waste Storage Depot, South Jakarta. This change occurs because there is a relationship of internal commitment to plastic waste management. The community feels the management of plastic waste at the Rawajati Waste Storage Depot, South Jakarta, by reducing the sight of piled up rubbish and unpleasant odors and using plastic waste to make other materials or be recycled at the Rajawati waste bank.